2019
DOI: 10.1002/cssc.201900241
|View full text |Cite
|
Sign up to set email alerts
|

A Cobalt‐Free Li(Li0.17Ni0.17Fe0.17Mn0.49)O2 Cathode with More Oxygen‐Involving Charge Compensation for Lithium‐Ion Batteries

Abstract: High‐energy‐density and low‐cost lithium‐ion batteries are sought to meet increasing demand for portable electronics. In this study, a cobalt‐free Li(Li0.17Ni0.17Fe0.17Mn0.49)O2 (LNFMO) cathode material is chosen, owing to the reversible anionic redox couple O2−/O−. The aim is to elucidate the Fe‐substitution function and oxygen redox mechanism of experimentally synthesized Li(Li0.16Ni0.19Fe0.18Mn0.46)O2 by DFT. The redox processes of cobalt‐containing Li(Li0.17Ni0.17Co0.17Mn0.49)O2 (LNCMO) are compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Our previous works indicated that voltage fade was significantly suppressed by replacing Co with Fe 35 , 36 . Unfortunately, the low coulombic efficiency during cycling has always existed but is rarely reported in Fe-substituted Li-rich cathode materials 20 , 43 – 45 , which inevitably gives rise to poor cyclic performance and reduces battery life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous works indicated that voltage fade was significantly suppressed by replacing Co with Fe 35 , 36 . Unfortunately, the low coulombic efficiency during cycling has always existed but is rarely reported in Fe-substituted Li-rich cathode materials 20 , 43 – 45 , which inevitably gives rise to poor cyclic performance and reduces battery life.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous works 35 , 36 , we found that the substitution of Co with Fe in Li-rich (Fe-Li-rich) materials can inhibit the formation of peroxy bonds and phase transformation, resulting in less voltage fade and the better capacity retention. The Fe-Li-rich is becoming a competitive candidate for the next generation of cathode material for its huge cost advantage.…”
Section: Introductionmentioning
confidence: 96%
“…We adopted the spin-polarized generalized gradient approximation (GGA) + U method with Perdew−Burke−Ernzerhof (PBE) exchange correlation function, 61 where the U values were 4.9 and 6.0 eV for Mn and Ni in the Li 28 Ni 6 Mn 14 O 48 system, respectively, similar to our previous work. 62 We relaxed the atomic position and lattice constant, and the convergence standards of energy and force were set to 10 −4 and 0.01 eV/Å, respectively. A 2 × 1 × 4 Monkhorst−Pack K-point mesh was applied to structural optimization with 96 atom positions.…”
Section: Methodsmentioning
confidence: 99%
“…As such, they obtained an excellent first discharge capacity (~232 mAhg −1 ) and reduced potential fading upon cycling thanks to the suppression of Ni-ion migration from the TM layer to the Li one. Wei et al [91] determined, using computational and experimental techniques, that the presence of Fe 3+ in the LRLO lattice contributes to stabilize oxidized oxygen species in particular by avoiding the accumulation of dimers, thus enhancing the structural stability of the de-lithiated LRLO. Recently, Pham et al [92], by combining operando OEMS (online mass spectrometry) and EIS (electrochemical impedance spectroscopy) experiments, proved the gas evolution of CO 2 , O 2 and POF 3 upon the first charge and matched the gaseous release with interface resistance modification at the cathode-electrolyte interface for an iron-doped LRLO with formula Li 1.16 Ni 0.19 Fe 0.18 Mn 0.46 O 2 .…”
Section: Co-free Lrlosmentioning
confidence: 99%